PENGARUH NAUNGAN DAN PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL LIDAH BUAYA (Aloe vera var. chinensis) - ENDRIANI ENDRIANI (Jurnal Ilmiah Pertanian, 2007)
ABSTRACTThe experiment was conducted at Cikarawang Experimental Farm of IPB from September 2004to Juni 2005. The experiment was arranged on Split Plot Design, the main plot was shading (0%, 50 % and 75 %) and the sub plot was the kinds of stable manure (control, chicken, sheep andcasting) with three replications. Each treatment consisted of 12 plants.The results indicated thatat the early growth, shading significantly increased plant growth. There was no interaction betweenshade and stable manure on parameters of leaf number, chlorophyl a, chlorophyl b and totalchlorophyl. The shading combined with stable manure application significantly increased plantheight, leaf length, leaf size, leaf area at the early growth. At the end this research without shadingtreatment (0 %) gave better growth. Those were showed on plant height and leaf length 4.9 %and 13.4 %, leaves number 9.8 %, leaf size 8.7 % and 25.8 %, and leaf area 6.0 % and 23.0 %higher compared 50 % shade and 75 % shade. The noshade and chicken manure gave the bestgrowth.